Morphology-dependent near-infrared photothermal activity of plasmonic TiN nanobars and nanospheres for anticancer, antibacterial therapy and deep in vivo photoacoustic imaging - Katerina Polakova; Sourav Rej; Sarka Hradilova; Jan Belza; Tomas Malina; Katerina Barton Tomankova; Renata Vecerova; Petr Matous; Petr Paral; Ariana Opletalova; Jana Soukupova; Tomas Pluhacek; et al. (Applied Surface Science Advances)
Plasmonic titanium nitride (TiN) nanoparticles are emerging nanomaterials possessing several orders of magnitude higher absorption cross section, but also exhibit higher photostability compared to conventional photosenzitizers. In the recent years, TiN has emerged as a highly effective electrocatalytic and environmentally friendly material with good biocompatibility. Its unique physicochemical properties and cost-effectiveness are essential for wide utilization in biomedicine. However, the effect of morphology of TiN on the photothermal therapy (PTT) efficiency has not been studied yet. Here, TiN nanocrystals of two precisely defined morphologies - nanobars and nanospheres - were prepared by unique pseudomorphic conversion of TiO2 nanowires and nanospheres via nitridation at 800 °C. Due to their multiple plasmonic resonances, the resulting materials show broad optical absorption spanning the entire solar spectrum and biological window including the NIR-I (750 – 1000 nm) and NIR-II (1000 – 1350 nm). Using low power illumination 318 mW/cm2 and NIR LED irradiation 940 nm, we observed a morphology-dependent PTT bioactivity, with the TiN nanobars being more efficient in cancer HeLa cells killing, while nanospheres showed higher antimicrobial activity toward Staphylococcus aureus and Escherichia coli bacteria strains. Moreover, acute and long-term in vitro biocompatibility together with in vivo monitoring of biodistribution showing enhanced permeability and retention (EPR) effect were confirmed by photoacoustic (PA) imaging in tumor bearing mice (C57BL/6J albino, EL4 lymphoma cell line). Thus, both TiN morphologies - nanobars and nanospheres are promising candidates in theranostic application via PTT therapy and PA imaging.